Cognitive Virtual Network Operator Games - Duan, Lingjie; Huang, Jianwei; Shou, Biying; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
This SpringerBrief provides an overview of cognitive mobile virtual network operator$1 (Bs (C-MVNO) decisions under investment flexibility, supply uncertainty, and market competition in cognitive radio networks. This is a new research area at the nexus of cognitive radio engineering and microeconomics. The authors focus on an operator$1 (Bs joint spectrum investment and service pricing decisions. The readers will learn how to tradeoff the two flexible investment choices (dynamic spectrum leasing and spectrum sensing) under supply uncertainty. Furthermore, if there is more than one operator, we present analysis of the competition among operators in obtaining spectrum and pricing services to attract users. The brief is designed for professionals working with C-MVNOs. Succinct and practical, it will assist them in making optimal investments and pricing decisions. It will also be of interest to researchers.s
Overview -- Secondary Spectrum Market Under Supply Uncertainty -- Secondary Spectrum Market Under Operator Competition -- Conclusion.
Keywords: Engineering; Computer Communication Networks; Microwaves; Telecommunication; Production of electric energy or power; Engineering; Communications Engineering, Networks; Computer Communication Networks; Power Electronics, Electrical Machines and Networks; Microwaves, RF and Optical Engineering